Synthesis and Biological Activities of some New Series of Azoles - Hallur, M.S.; Sangepure, S.S. (Asian Journal of Chemistry, 2010)
The reactions of 2-naphthoxy acetate and ethyl salicylate with hydrazine hydrate gave the corresponding hydrazides. Substituted pyrazoles were synthesized by treating the carbohydrazides with ethylacetoacetate, acetylacetone and ethylcyanoacetate. Cyclisation of thiosemicarbazides under appropriate conditions afforded triazole and thiadiazole derivatives. All the compounds were tested for their antimicrobial and antifungal activities.